Nurse-Engineer Opportunities and Education in The Post-Pandemic Nursing Care - Rino Ferdian Surakusumah; Rifa Yanti; Icha Fatwasauri (Universitas STRADA Indonesia, 2021)
Nurses are one of the frontline professions in dealing with patients affected by Covid-19. Nurses are dealing directly with problems that occur in covid-19 health services. This challenge is an opportunity for the emergence of the competence development of the nursing profession by implementing technological competency. If a nurse has technological competence, they are expected to produce appropriate technological innovations. This paper discusses the opportunities of nurses to implement engineering competency in order to improve innovation opportunities in post-pandemic nursing care. Technological, economic, regulatory, and sociological forces that influence the transformation of the nursing profession into nurse-engineers will be explained below with a new collaborative nurse-engineer educational competencies are also proposed.